Robust Synchronization of the Unified Chaotic System - Hatem Trabelsi; Mohamed Benrejeb (Institute of Advanced Engineering and Science, 2015)
The paper investigates the synchronization problem of the unified chaotic system. The case of identical, but unknown master and slave unified chaotic systems is considered. Based on compound matrices formalism, a unified synchronization control scheme is proposed independently of the unknown system parameter. Simulation results are provided to show the effectiveness of the presented scheme.